Effects of pasture stockpiling times on forage yield and chemical composition of elephant-grass cv. Mott - de Lucena Costa, Newton; Ribamar da Cruz Oliveira, José; Ramalho Townsend, Claudio (Pesquisa Agropecuaria Brasileira, 1998)
An experiment was conducted in Porto Velho, Rondônia, with the purpose of determining the best time for pasture recuperation and of consumption of the accumulated forage of elephant-grass (Pennisetum purpureum cv. Mott) for herd supplementation in the dry season. The experimental design was in randomized complete blocks (split-plot) with three replicates. The periods of stockpiling began on February 28, March 28 and April 28 and constituted the main plots; and the consumption months (June 30, July 30, August 30 and September 30), the subplots. The data indicate the feasibility of stockpiling of the grass during the rainy season, to provide forage for herd supplementation in the dry season. The highest dry matter (DM) yields were obtained with the pasture stockpiled in February or March and consumption in August or September. The grass, irrespective of stockpiling periods, showed significative reductions (P<0.05) in crude protein contents and in vitro DM digestibility toward the later consumption time. In order to obtain greater forage yields with better quality, it is suggested that stockpiling begin in March for forage consumption in June or July, and in April for forage consumption in August or September.